Functional osteoclastogenesis: the baseline variability in blood donor precursors is not associated with age and gender - Pivetta, Eliana (Oncotarget, 2015)
Mononuclear osteoclast precursors circulate in the monocyte fraction of peripheral blood and form multinuclear cells with all osteoclastic phenotypic characteristics when cultured in the presence of macrophage colony stimulating factor (M-CSF) and receptor activator of nuclear factor kB ligand (RANKL). The method to obtain osteoclast precursors from peripheral blood is simple but the number of recovered osteoclasts is often largely insufficient for functional analyses. The original aim of this study was to develop a rapid and efficient method that could overcome the donor variability and enrich the osteoclast precursors from a small volume of peripheral blood as a basis for future clinical studies to correlate the differentiation potential of circulating osteoclast precursors with bone lesions in cancer patients. We improved the efficiency of osteoclastogenesis by reducing isolation and purification times and overcame the use of flow cytometry and immunomagnetic purification procedures. In our culture system the osteoclast number was increased several-fold and the precursors were able to reach a full differentiation within seven days of culture. Both age as well as gender differences in osteoclastogenesis efficiency were no longer evident by processing limited volume blood samples with this simple and rapid method.